Acumulação primitiva: um processo atuante na sociedade contemporânea - Sandra Lencioni (Confins)
With the hegemony of the social accumulation reproduction, the primitive accumulation is interpreted sometimes like a fact of the past and sometimes like a process that continues until today. Our point of view is that the historical primitive accumulation has not disappeared, including being one of the important components of contemporary society. In this society, the capitalist processes of primitive accumulation and the reproduction of capital coexist and complement each other in a contradictory and dialectical way. The first, the process of primitive accumulation is related to spoliation and to the production of new capital, while the second, the reproduction of capital is related to the exploration and it is a part of a capital already existing. The difference between the names 'spoliation' and 'exploitation' is confronted and the Harvey's opinion about accumulation by dispossession is discussed in the first part of the text. The second part discusses about the primitive accumulation of today, repeating the fraud, the theft and the violence, that were presents in the moment of the genesis of capitalism. Although the world seems to have changed, with both technical advancement and a variety of laws about human rights, it has not changed that much. Acts of fraud, theft and violence as expedients to generate capital still continues. Several examples of robbery of the natural resources are given, including the bio-piracy. Also, the debt slavery is emphasized as a violent form of spoliation, a form of primitive accumulation of capital in which the free worker, by mechanisms of subjection which he is subjugated, loses his freedom. The theft of land constitutes another example of primitive accumulation of the contemporary society. It is stated that all forms of dispossession are producing money and producing potential capital. Particularly, the financial capital is the one that especially establishes the link between primitive accumulation and reproduction of capital in contemporary society.